Angel and devil: the protective immunity and pathogenic inflammation of tissue resident memory T cells in ulcerative colitis - Wang, Xintong; Zhang, Jiaqi; Fang, Lihui; Tang, Xudong (Frontiers in Immunology, 2025)
Ulcerative colitis (UC) is an incurable autoimmune disease. Patients with UC endure the burden of recurrent flare-ups and face a substantial economic burden due to long-term medication. The complex etiology and unclear pathogenesis pose a significant challenge to the development of effective and curative treatments. Recent research indicates that local memory at the site of inflammatory intestinal mucosa in UC is closely associated with the persistent presence of tissue-resident memory T (TRM) cells. TRM cells, a subset of memory T cells, exhibit long-lived, low-migration characteristics. These cells reside in tissues, where they provide immediate immune protection while also contributing to chronic, localized inflammation. The presence of TRM cells in the inflamed intestinal mucosa of UC patients is a crucial factor in the recurrence of the disease. However, the process involved in the formation and differentiation of TRM cells within the intestinal mucosa remains poorly understood. Various surface markers, transcriptional networks, and signaling pathways regulate the formation and maintenance of TRM cells in the intestine. To further understand the role of TRM cells in UC pathogenesis, we have summarized the latest findings to pave the way for the development of future targeted therapies.